Pengaruh Tingkat Ketergantungan Penggunaan ChatGPT terhadap Pemahaman Pembelajaran Siswa SDN 2 Sindangpanon Purwakarta - Erni Najiatusalamah; Yuni Fitriani; Safitri linawati (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
Advances in Artificial Intelligence (AI), particularly ChatGPT, have been utilized as a learning aid because it can provide information quickly and help students complete their assignments. However, excessive use can lead to dependency, which has the potential to affect students’ learning comprehension. This study aims to determine the effect of the level of dependence on ChatGPT use on students’ learning comprehension at SDN 2 Sindangpanon Purwakarta. The study employed a quantitative approach using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS. The study sample consisted of 61 students selected using a saturation sampling technique. Data were collected via a Likert-scale questionnaire comprising 12 statements. The results indicate that the level of dependence on ChatGPT has a negative and significant effect on students’ learning comprehension, with a path coefficient of -0.375, T -statistic of 2.571, a P-value of 0.010, and an R-squared of 0.140. Thus, the level of dependence on ChatGPT use explains 14% of the variation in students’ learning comprehension, while 86% is influenced by other factors outside the scope of this study that were not analyzed in depth.